STUDYING THE ANTIOXIDANT ACTIVITY OF THE FOOD ADDITIVE “AS-AN” OBTAINED FROM THE PLANTAGO MAJOR (Scientific journal of the Fergana State University, 2023)
This article describes some of the causes of peptic ulcers and synthetic medecines used in its treatment. In order to determine the antioxidant activity of the new food additive "Ac-AN", the results of studies conducted with inhibition of the autoxidation reaction in vitro are discussed.